The Bean Impact Project in numbers: Activities and projected outputs - Martinez Rioja, Jose Maria; Reyes Padilla, Byron Alejandro; Gomez Centeno, Lorena Belixa; Maredia, Mywish K. (2022)
The objective of this study is to estimate the economic impact of investments made by the former Legume Innovation Lab program, the International Center for Tropical Agriculture (CIAT) and other organizations and universities on bean breeding. The evaluation focuses on the USA (i.e., Michigan), Guatemala, Honduras, Nicaragua and Haiti. We present infographis summarizing the preliminary findings to mid-2022 and projected outputs. In this study, we rely on a combination of secondary data and expert opinion data (mostly), primary (farmer-level) data from two countries, and field trials data from two countries to estimate yields farmers obtain under their conditions.